Comparison of Ground-Based Measurement Results of Total Ozone near St. Petersburg - Nerobelov, G. M.; Al-Subari, O.; Timofeyev, Yu. M.; Virolainen, Ya. A.; Poberovskii, A. V.; Solomatnikova, A. A. (Izvestiya. Atmospheric and oceanic physics, 2022)
This paper compares the results of ground-based measurements of the total ozone content (TOC) near St. Petersburg for the period of 2009–2020. The Dobson spectrophotometer and the M-124 filter ozonometer are located in the village of Voeikovo; the Bruker 125HR Fourier spectrometer is in Peterhof about 50 km from Voiekovo. A comparison of the results of average daily TOC measurements with different instruments over almost 300 days of observations showed that the mean difference and standard deviation of the differences between the Dobson and Bruker measurements are –12.9 ± 9.3 DU (–3.7 ± 2.7%), between Dobson and M-124 0.1 ± 7.7 DU (0.0 ± 2.2%), and between M-124 and Bruker –12.9 ± 10.6 DU (–3.7 ± 3.0%). The systematic overestimation of the Bruker data compared to the Dobson and M-124 data can be caused both by the spatiotemporal mismatch of the measurements (Voeikovo is more often subject to anthropogenic pollution, while background air masses are mainly observed in Peterhof), and by the difference in spectroscopic parameters in the IR and UV regions of the spectrum. The scatter of data between different ensembles of TOС measurements does not exceed the measurement errors of the methods. The temporal change in the average monthly TOС according to the data of three sets of ground-based measurements in the region of St. Petersburg did not show a clear gradual year-to-year increase or decrease in the gas content over the period 2009–2020.